Compressive imaging using fast transform coding - Thompson, A; Calderbank, R (Society of Photo-Optical Instrumentation Engineers, 2016)
We propose deterministic sampling strategies for compressive imaging based on Delsarte-Goethals frames. We show that these sampling strategies result in multi-scale measurements which can be related to the 2D Haar wavelet transform. We demonstrate the effectiveness of our proposed strategies through numerical experiments.